Analisis Dampak Bermain Game Online Free Fire Terhadap Intraksi Sosial Anak Sekolah Dasar di Desa Jekulo - Suryakusuma, Ega; Ismaya, Erik Aditia; Kuryanto, Muhammad Syaffruddin (PGSD Universitas Muria Kudus, 2024)
This research aims to determine the impact of playing the online game Free Fire on the social interactions of elementary school aged children in Jekulo Village.The method used in this research is a qualitative descriptive approach to understand a phenomenon experienced by the subjects in the research. This research was conducted in Jekulo Village, with research subjects consisting of elementary school age children and their parents in Dukuh Karang in Jekulo Village. This research uses observation techniques, in-depth interviews, activity documentation, and recording as data collection methods. The data analysis technique for this research is carried out by reducing data, presenting data, and drawing conclusions. Data validity tests in this research include credibility, transferability, reliability and confirmability tests.The research results show that the online game Free Fire has an impact on the social interactions of children in Jekulo village. This impact has both positive and negative impacts and depends on how children play online games properly and correctly. The negative impact that is commonly found is that children tend to prefer playing games rather than talking with their parents or family. This causes children to be unable to exchange stories and strengthen relationships with their families.